Adipose-Derived Mesenchymal Stem Cells Accelerate Diabetic Foot Ulcer Healing by Promoting Macrophage M2 Polarization Through Downregulation of EREG and CSTA - Cao J; Zhang X; Li Z; Zhang S; Guo L; Liu Z; An W; Xu L; Li L; Long X; Yang Y (Journal of Inflammation Research, 2025)
Jing Cao,1,* Xin Zhang,1,* Zhujun Li,2 Sen Zhang,3 Leiming Guo,1 Zichao Liu,1 Wenqiang An,1 Lijia Xu,4,5 Lijie Li,1 Xiao Long,2 Yuemei Yang1 1Research and Development Department, Beijing AegleStem Therapeutics Co., Ltd., Beijing, People’s Republic of China; 2Department of Plastic Surgery, Peking Union Medical College Hospital, Beijing, People’s Republic of China; 3Institute of Materia Medica, Chinese Academy of Medical Sciences & Peking Union Medical College, Beijing, People’s Republic of China; 4Institute of Medicinal Plant Development, Chinese Academy of Medical Sciences & Peking Union Medical College, Beijing, People’s Republic of China; 5Hainan Branch of the Institute of Medicinal Plant Development, Chinese Academy of Medical Sciences & Peking Union Medical College, Haikou, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yuemei Yang, Research and Development Department, AegleStem Therapeutics Co., Ltd.E4, Innovation Service Center, Free Trade Zone, 1 North Yuanping Road, Beijing, 102600, People’s Republic of China, Email maeyang@aeglestem.com Xiao Long, Department of Plastic Surgery, Peking Union Medical College Hospital, 1 Shuaifuyuan, Beijing, 100730, People’s Republic of China, Email pumclongxiao@126.comPurpose: Macrophage polarization plays a critical role in the chronic wound healing of diabetic foot ulcers (DFU). Recent studies have shown that adipose-derived mesenchymal stem cells (ADSCs) can reduce inflammation in DFU and promote wound healing. Despite advances in stem cell therapy, the molecular mechanisms by which ADSCs regulate macrophage polarization in DFU healing remain unclear, and robust prognostic models for DFU are lacking. This study aims to identify macrophage polarization-associated molecules in DFU and explore whether ADSCs promote DFU healing by regulating these molecules.Patients and Methods: Macrophage polarization-associated differentially expressed genes (MA-DEGs) were screened from GSE134431 and GSE80178 datasets. Protein-protein interaction (PPI) networks were constructed using STRING and Cytoscape. Machine learning and Firth regression were employed to develop a prognostic model, which was evaluated using receiver operating characteristic (ROC) curves. The expression of predicted genes (EREG and CSTA) and the regulatory effects of ADSCs on these genes were validated in both DFU mouse model and THP-1 cells.Results: A total of 30 macrophage polarization-associated differentially expressed genes (MA-DEGs) were identified, including 18 hub genes. These MA-DEGs were primarily enriched in pathways related to leukocyte chemotaxis and interleukin-4 and 13. A two-gene prognostic model was constructed using machine learning and Firth regression, achieving an AUC greater than 0.944 in both the training and external validation datasets. In vivo and in vitro experiments demonstrated that ADSCs regulate EREG and CSTA expression to promote macrophage M2 polarization and facilitate DFU wound healing.Conclusion: This study elucidates the molecular mechanisms by which ADSCs facilitate DFU healing via macrophage M2 polarization. The identified two-gene MA-DEGs model not only serves as a potential prognostic biomarker but also provides promising targets for DFU therapy.Keywords: diabetic foot ulcer, macrophage polarization, prognostic model, adipose-derived mesenchymal stem cells